DIAGNOSIS AND PREVENTION OF CARDIOTOXICITY IN PATIENTS WITH BREAST CANCER FROM THE STANDPOINT OF AN ONCOLOGIST AND A CARDIOLOGIST - T. Yu. Semiglazova; G. M. Teletaeva; N. A. Kozyavin; A. V. Zagatina (Опухоли женской репродуктивной системы)
Knowledge of anthracycline antibiotics’ (AAs) pathogenesis and main risk factors allowed to develop various methods of prevention and early detection of cardiotoxicity as well as to create several guidelines on decreasing the risk of its development. Traditional AAs are a crucial option in treatment of metastatic breast cancer including their repeated prescription. However, their application is significantly limited by various manifestations of toxicity, especially cumulative cardiotoxicity. The most promising is use of pegylated liposomal pharmaceutical formulations of AAs. Among these formulations, pegylated liposomal doxorubicin almost fully lacks anthracycline cardiotoxicity because due to its unique formulation it accumulates almost exclusively in tumor tissue.